2005
DOI: 10.1080/00480169.2005.36579
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent gastro-oesophageal intussusception, trichobezoar and hiatal hernia in a cat

Abstract: Gastro-oesophageal intussusception is a rare condition in cats. Its aetiology in relation to a pre-existing hiatal hernia and a trichobezoar is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 13 publications
0
31
0
2
Order By: Relevance
“…Some authors have suggested a relation with diverse esophageal abnormalities such as megaesophagus [8,10,12], incompetence of the lower esophageal sphincter which often occurs secondary to sliding hiatal hernias, different causes of increased intrabdominal pressure such as chronic vomiting or blunt trauma, and negative intrathoracic pressure from inspiratory dyspnea due to chronic upper airway obstruction or severe respiratory disease [6,10].…”
Section: Case Presentationmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors have suggested a relation with diverse esophageal abnormalities such as megaesophagus [8,10,12], incompetence of the lower esophageal sphincter which often occurs secondary to sliding hiatal hernias, different causes of increased intrabdominal pressure such as chronic vomiting or blunt trauma, and negative intrathoracic pressure from inspiratory dyspnea due to chronic upper airway obstruction or severe respiratory disease [6,10].…”
Section: Case Presentationmentioning
confidence: 99%
“…On the principal international scientifi c databases, there are only fi ve clinical cases of GEI in domestic cats reported between 1998 to 2015 in domestic shorthair cats [5,7,8], in a Himalayan [4] and in a Birman [6], including four males and one female; two were kittens, two adults and the last an elder cat, age ranged from 4 months to 15 years old. The clinical cases presented different clinical signs referring to gastrointestinal symptoms such as vomitus or regurgitation [6][7][8] or respiratory disease such as respiratory distress, open-mouth breathing, inspiratory stridor and mucopurulent nasal discharge, with acute or intermittent presentation [4,8].…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations